MUHAMMADIYAH DAN GERAKAN PENCERAHAN - Dartim Dartim; Dodi Afianto (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2016)
Muhammadiyah is the Islamic movements that make Islam as the soul in any aspects of life. complexity of the faith problems dan Muamalah that hit people make Muhammadiyah should be able to be creative in da'wah. The challenge in keeping Islam in order to become a genuine religion of various forms of shirk and hypocrisy is still relevant. New TBC styles or modern TBC, such as secularism, liberalism, materialism, syncretism and relativism, and other isms that it is shirk and modern hypocrite which are no less dangerous than the traditional TBC. In addition the problem of poverty, economic disparities, pornography, crime and other social problems remains a heavy burden for the nation. Islamic progressive of Muhammadiyah as a trade mark in this period is a movement of enlightenment for the people and nation.